2009
DOI: 10.1021/jm900286j
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the First Highly M5-Preferring Muscarinic Acetylcholine Receptor Ligand, an M5 Positive Allosteric Modulator Derived from a Series of 5-Trifluoromethoxy N-Benzyl Isatins

Abstract: This report describes the discovery and initial characterization of the first positive allosteric modulator of muscarinic acetylcholine receptor subtype 5 (mAChR5 or M5). Functional HTS, identified VU0119498, which displayed micromolar potencies for potentiation of acetylcholine at M1, M3, and M5 receptors in cell-based Ca2+ mobilization assays. Subsequent optimization led to the discovery of VU0238429, which possessed an EC50 of approximately 1.16 µM at M5 with >30-fold selectivity versus M1 and M3, with no M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 13 publications
1
98
1
Order By: Relevance
“…In the application of allosteric theory, the focus has usually been on binding cooperativity, a point embodied in the TCM in which the binding cooperativity is a shared modulatory value that the two ligands possess when they are bound to a common receptor. However, it is recognized that allosteric ligands are capable of modulating efficacy (Ehlert, 1988), and a number of groups have observed allosteric modulation of agonist efficacy at GPCRs (Urwyler et al, 2003;Sharma et al, 2008;Bridges et al, 2009). Our previous studies found that amiodarone was able to allosterically enhance agonist-stimulated response at the M 5 receptor, without any potency enhancement.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the application of allosteric theory, the focus has usually been on binding cooperativity, a point embodied in the TCM in which the binding cooperativity is a shared modulatory value that the two ligands possess when they are bound to a common receptor. However, it is recognized that allosteric ligands are capable of modulating efficacy (Ehlert, 1988), and a number of groups have observed allosteric modulation of agonist efficacy at GPCRs (Urwyler et al, 2003;Sharma et al, 2008;Bridges et al, 2009). Our previous studies found that amiodarone was able to allosterically enhance agonist-stimulated response at the M 5 receptor, without any potency enhancement.…”
Section: Discussionmentioning
confidence: 98%
“…It is believed that targeting regions of the receptor with greater sequence divergence (i.e., allosteric sites) will facilitate the discovery of more subtype-selective compounds and allow therapeutic exploitation of the different subtypes (Wess et al, 2007;Langmead et al, 2008). In agreement with this view, the current set of subtype-selective ligands generally act at allosteric sites (Shirey et al, 2008;Bridges et al, 2009;Marlo et al, 2009). …”
Section: Introductionmentioning
confidence: 92%
“…For example, pharmacological activation of M 5 receptors may be useful to increase cerebral perfusion in certain pathophysiological conditions, such as Alzheimer's disease and cerebral ischemia (37,41). Interestingly, several agents have been described recently that can selectivity enhance signaling through M 1 or M 5 receptors (4,8,27,40). Such ligands may become relevant for the development of novel muscarinic drugs aimed at modulating local perfusion.…”
Section: Perspectivesmentioning
confidence: 99%
“…A key bottleneck to research and therapeutic development efforts for the muscarinic ACh receptor family has been the lack of receptor subtype-selective pharmacological tools to help determine the physiologic relevant family member(s) to target for various indications. However, over the past decade, several muscarinic subtype-selective small molecule ligands have emerged through the successful targeting of unique allosteric binding sites generally located on the exterior surface loops of the receptors [e.g., M 1 (Daval et al, 2013), M 2 (Huang et al, 2005), M 4 (Nawaratne et al, 2010), M 5 (Bridges et al, 2009)]. Within this work, we characterize the allosteric-site ligand LY2119620 (3-amino-5-chloro-N-cyclopropyl-4-methyl-6-[2-(4-methylpiperazin-1-yl)-2-oxoethoxy] thieno[2, 3-b]pyridine-2-carboxamide) and demonstrate that it is a high-affinity M 2 /M 4 receptor-selective positive allosteric modulator (PAM).…”
Section: Introductionmentioning
confidence: 99%